An Assessment of Hurricane Charley's Impact on Cuba - William A. Messina, Jr. (EDIS)
Reports and information from Cuba on the damage from Hurricane Charley have been limited. However, in an effort to be responsive to inquiries about storm damage in Cuba, this report attempts to compile the limited amount of information that is available from the press and through personal communication with colleagues in Cuba with knowledge of Cuba's economy and agricultural sector, developed over the past 10 years of research on Cuba conducted by the University of Florida's Institute of Food and Agricultural Sciences (UF/IFAS) Food and Resource Economics Department, to offer our assessment of the situation in Cuba following Hurricane Charley. This is EDIS document FE494, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, UF/IFAS, University of Florida, Gainesville, FL. Published September 2004.